PENGARUH KINERJA KEUANGAN, DEBT DEFAULT DAN REPUTASI KANTOR AKUNTAN PUBLIK TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN - Susanto, Putri Ragillia; Zubaidah, Siti (Jurnal Reviu Akuntansi dan Keuangan)
This study aims to examine the effect of financial performance, debt default and reputation ofpublic accounting firm on acceptance of going concern audit opinion. The method of this researchis a quantitative approach and SPSS as an analysis tool. The results showed that the financialperformance proxied by the calculation of financial ratios has no significant and negative effecton the acceptance of going concern audit opinion. Second, the company’s default debt has nosignificant and positive effect on the acceptance of going concern audit opinion. Finally, thereputation of the public accounting firm proxied at the scale of the public accounting firm has nosignificant and positive effect on the acceptance of going concern audit opinion.Ke ywords: Debt Default, Financial Performance, Going Concern, Reputation of Public Accounting Firm